TRANSFORMASI PENDIDIKAN DI PONDOK PESANTREN DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) : KAJIAN SISTEMATIS TERHADAP INOVASI DI ERA DIGITAL - Ubaidillah, Moch; Ismawati (As-Sulthan Journal of Education, 2025)
This study analyzes educational innovations in pesantren to achieve Sustainable Development Goal 4 (SDG 4) on quality education while preserving traditional values. The study aims to identify modernization strategies aligned with local wisdom to ensure effective innovation without compromising pesantren identity. The research employs a systematic literature review of six relevant studies discussing life skills integration, flexible curricula, digitalization, and the utilization of digital waqf in pesantren education. The findings reveal that pesantren education innovations include digital literacy implementation, student entrepreneurship development, and technology adoption in learning. However, key challenges include infrastructure limitations, human resource readiness, and cultural resistance to change. This study concludes that a data-driven approach is essential in curriculum design, strengthening digital infrastructure, and developing an evaluation system that balances modernization with traditional values. With the right strategies, pesantren can continue contributing to quality education that remains relevant in contemporary times.